Suitability, scalability, and sustainability of community health worker led task sharing for hypertension in Nepal: a rapid review - Sagtani, Reshu Agrawal; Shrestha, Archana (International Journal Of Community Medicine And Public Health, 2025)
This review aims to explore the suitability, scalability, and sustainability of task sharing through female community health volunteers (FCHVs) in Nepal's healthcare system, focusing on hypertension (HTN) prevention and management. The published secondary literature and reports were searched for identifying national examples of task sharing and systematically identify critical factors influencing the success of task sharing in the Nepalese context. The roles of FCHVs are currently being explored for prevention and management of chronic diseases including HTN due to their community reach and trust. Evidence shows short term cost-effectiveness of task sharing through FCHVs for HTN. However, while their widespread presence supports scalability, systemic barriers like policy gaps and supply chain issues remain. Sustainability hinges on consistent training, integration into the formal health system, and financial incentives to maintain long-term impact. To ensure suitability, scalability, and sustainability of task sharing through FCHVs for HTN in Nepal, a comprehensive strategy comprising of a stable financial model, continuous capacity building, robust community engagement, and strong policy support is crucial.